Encyclopedia of detail in contemporary residential architecture - McLeod, Virginia (London : Laurence King, 2010)
"This comprehensive reference contains more than 700 scale drawings of every type of detailing used in residential architecture, drawn from 100 of the best recent architect-designed houses from around the world. ... and includes a bonus CD containing all of the drawings featured in the book"--P. [4] of cover.
System requirements for accompanying CD-ROM: IBM PC or Macintosh; drawings are supplied in two versions: files with the suffix ".eps" are 'vector' Illustrator EPS files but can be opened using other graphics programs such as Photoshop; files with the suffix ".dwg" are generic CAD format files and can be opened in a variety of CAD programs.
Accompanying CD-ROM system requirements
Keywords: Architecture, Domestic -- Designs and plans; Architect-designed houses -- Designs and plans; Architecture -- Details; Architectural drawing -- 21st century